Global issues - Clarke, Calvin; Clarke, Susie (National 4 & 5 geography, 2018)
Exam Board: SQA Level: National 5 Subject: Geography First Teaching: September 2017 First Exam: Summer 2018 This second edition now includes N5 examination-style questions, together with detailed advice on answering them, as well as exemplar answer, included for every topic. - Now includes the Natural Regions topic - Covers Climate Change, Health and Environmental Hazards - Natural Regions topic takes the place of Trade and Globalisation